Oral insulin delivery using artificial peptide - Adikane, V. Harshavardhan (Indian Journal of Biochemistry & Biophysics, 2021)
The daily multiple insulin injection is the line of treatment for diabetes mellitus. As the oral insulin delivery mimics, the physiology of endogenous insulin secreted by pancreas. Recently, the search for suitable carrier to develop oral insulin delivery has been intensified. However, the carrier toxicity and very less bioavailability of insulin remains the major problem in the development of oral insulin delivery. Preparation of a non-covalent insulin-peptide complex using different peptide made of 16 to 20 L-amino acids studied to overcome the problem. The in vitro testing of insulin-peptide complex showed significant stability against the proteolytic enzyme. Whereas, in in vivo testing, the presence of 10-41% insulin in blood plasma observed after 30 to 60 min oral feeding of insulin-peptide complex. Results indicated that the peptide which showed moderate protection against pepsin and minor protection against trypsin and chymotrypsin has an important role in enhancing oral insulin bioavailability. However, the peptide which showed higher protection against trypsin and no protection against pepsin could not achieve significant oral insulin bioavailability.
Keywords: Bioavailability; Carrier toxicity; Insulin-peptide complex; Oral insulin delivery; Proteolytic enzyme resistance

Novel cocrystal of quercetagetin: in vitro and in vivo insights into biopharmaceutical performance - Suryawanshi, Smita; Shaligram, Parth; Gonnade, Rajesh G.; Patil, Sharvil (Pharmaceutical Research, 2026)
Purpose Quercetagetin (QTGN) is a naturally occurring flavonol predominantly sourced from marigold flowers and possesses notable therapeutic potential, including antidiabetic, anticancer, antioxidant, anti-inflammatory, and antiviral properties. However, poor aqueous solubility and in turn bioavailability restrict therapeutic utility of QTGN. Crystal engineering is one of the approaches proven to be fruitful in resolving the solubility issues of many active pharmaceutical ingredients (APIs). Method In the present work, a cocrystal of QTGN using betaine (BET) as coformer viz. Quercetagetin & sdot;betaine & sdot;ethanol (QTGN & sdot;BET & sdot;EtOH) was synthesized using the solvent evaporation method. It was further characterized using Fourier Transform Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), Thermogravimetric analysis (TGA), Powder X-ray diffraction (PXRD), and single crystal XRD (SCXRD). Result FTIR studies confirmed hydrogen bonding between QTGN and BET. PXRD studies showed formation of new crystalline phase. The prepared cocrystal had stoichiometric ratio of 1:1:1 between QTGN, BET, and ethanol forming cocrystal ethanolate and shared robust hydroxyl & ctdot;carboxylate supramolecular synthon as confirmed by TGA and SCXRD, respectively. Equilibrium solubility study and in vitro dissolution study showed a significant improvement (p < 0.0001) in aqueous solubility of QTGN upon its cocrystallization with BET. Furthermore, in vivo pharmacokinetic study revealed a 1.28-fold increase in bioavailability of QTGN when formulated as cocrystal solvate. The prepared cocrystal was found to be stable over a period of six months at 40 degrees C and 75% RH when analyzed using PXRD studies. Conclusion The current work represents a frontier in pharmaceutical formulation, providing a means to fully harness the therapeutic potential of QTGN using cocrystal approach.
Keywords: betaine; Bioavailability; cocrystal; quercetagetin; USP apparatus IV